Students’ Anxiety in Speaking Class: An Investigation in Online and Offline Learning System - Regita Septyani Rahmi; Banatul Murtafi'ah (Eduvelop: Journal of English Education and Development, 2022)
This study aims to investigate English Education students speaking anxiety in both online and offline learning contexts. This study did a further investigation about the strategies they use to cope with their anxiety when doing public speaking in both online and offline contexts. Although there is a lot of research regarding speaking anxiety has been done by the researchers both in Indonesia and other countries, there are still limited studies discussing speaking anxiety in education especially in both offline and online learning among English education students in Indonesia. This study employed a qualitative method. The data were collected through interviews with two students from a private university in Indonesia. The findings showed that both participants were less anxious when they do public speaking in the online context than in offline one. Furthermore, it was also found that these participants only used one strategy to overcome their anxiety (i.e., preparation) for online public speaking; and used more strategies (i.e., relaxation, preparation, positive thinking, audience depreciation, concentration, and resignation) to deal with offline speaking anxiety. Therefore, it is implied that through these coping strategies,